Phenomenological psychopathology of attention: between description and hermeneutics - Dos Santos, Hernani Pereira; Verissimo, Danilo Saretta [UNESP] (FapUNIFESP (SciELO), 2022)
This paper analyses the contributions of phenomenological psychopathology for the critical consideration of the phenomena of attention and inattention in the contemporary social and historical context. To achieve that goal, we analyzed the naturalist matrix of conception of attention and its dysfunction and situated phenomenological psychopathology. We present critical guidelines regarding the naturalistic conception of executive functions and their correlation with attentional processes and question descriptions of the inattentive subject’s experience. We further analyzed the social normativity of the attentive experience and its intersubjective and contextual criteria. Finally, we propose a hermeneutical approach regarding contemporary attention regime, which highlights the link between the experience of attentive failure and the demands of a world that has become increasingly faster and filled with stimuli.
La psicopatología fenemonológica de la atención: entre la descripción y la hermenéutica
Psychopathologie phénoménologique de l’attention: entre description et heméneutique
Keywords: attention deficit disorder with hyperactivity; Hermeneutics; phenomenological psychopathology; vigilance